Aplikasi teori sadd al-dzarī‘ah dan fatḥ al-dzarī‘ah ke dalam peraturan TIPIKOR di Indonesia - Nasrullah Rullah (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
The starting point of use between sadd and fatḥ is al-dzarī‘ah. In Madhab Mālik and Ḥanbālī, al-dzarī‘ah is prohibited and recommended. Al-Qarafī of Madhab Mālik and Ibn al-Qayyim of Madhab Hanbalī mention al-dzarī‘ah sometimes forbidden (called sadd al-dzarī‘ah) and are sometimes told (called fatḥ al-dzarī‘ah). In the study of fiqh jināyah (Islamic criminal law), the theory of sadd al-dzarī'ah and fatḥ al-dzarī'ahis still open to its development space, given the many ways in which criminal acts are carried out, such as corruption in Indonesia which has been rooted among officials. While the eradication is not maximal and requires a comprehensive set of regulations, so that various gaps in corruption in Indonesia can be indicated and all forms of disobedience to the state and people's welfare can be overcome because they contain greater values of maslahah. The two theories of Islamic criminal law, especially regarding sanctions for corruption, can be made possible in the law of eradicating corruption in Indonesia, thus creating anti-corruption laws in a stronger law enforcement process.